Morphology of Arctic cod (Boreogadus saida) assessed according to habitat preference and age in the Beaufort Sea - Juliano Malizia; Marie Launay; Ingrid Marie Bruvold; María Quintela; Torild Johansen; James D. Reist; Andrew R. Majewski; Denis Roy (Arctic Science, 2023)
The Arctic cod (Boreogadus saida (Lepechin, 1774)) represents the most widespread and abundant fish in the Arctic and is a critical trophic link in its ecosystems. Like many species endemic to the region, it has lost essential habitat as the extent and thickness of sea ice have declined substantially in recent decades. Extreme warming induced by climate change continues to deteriorate polar marine environments. Thus, understanding how Arctic cod use and partition their habitat/environment is central to their conservation. We assessed Arctic cod functional morphology using traditional (including gill rakers) and geometric morphometrics and explored whether these differed among primarily depth-based habitats and age classes using multivariate techniques. While distinct ecotypes have been proposed, these were not detected in our analyses. Rather, results show similar patterns in external morphology of Arctic cod across habitats and age classes in the Beaufort Sea. However, analysis of gill rakers revealed concurrent habitat- and age-specific changes likely associated with dietary preferences. Findings indicate that although Arctic cod do not specialise in external morphological features in any habitat, important aspects of their internal feeding morphology shift as they grow, likely underpinning important distributional shifts and its critical role in transferring energy in Arctic marine ecosystems.